Key Concepts in Traditional Chinese Medicine II - Zhaoguo, Li. author. aut Link
XIV, 125 p.
Keywords: This book offers an overview of Chinese medicine terminology translation, defining the central concepts in Chinese traditional medicine, providing simplified Chinese characters, Mandarin Pronunciation in pinyin, citations for 110 of the most key concepts in traditional Chinese medicine and culture. Covering definitions of terms relating to visceral manifestation, meridians, etiology, pathogenesis, and treatment principles in traditional medicine, it offers a selection of English versions of each term in addition to a standard of English version, drawing on the translation history of traditional Chinese medicine. It provides a useful resource to understand the fundamental terms of traditional Chinese medicine and culture in Chinese and English, and their relevance to cross-cultural discourse.